Practical use of polymer brushes in sustainable energy applications: interfacial nanoarchitectonics for high-efficiency devices. (13th December 2018) - Giussi, Juan M.; Cortez, M. Lorena; Marmisollé, Waldemar A.; Azzaroni, Omar
Abstract : Polymer brushes provide a new perspective from which to consider the development of energy conversion and storage devices with improved performance and efficiency. Abstract : The discovery and development of novel approaches, materials and manufacturing processes in the field of energy are compelling increasing recognition as a major challenge for contemporary societies. The performance and lifetime of energy devices are critically dependent on nanoscale interfacial phenomena. From the viewpoint of materials design, the improvement of current technologies inevitably relies on gaining control over the complex interface between dissimilar materials. In this sense, interfacial nanoarchitectonics with polymer brushes has seen growing interest due to its potential to overcome many of the limitations of energy storage and conversion devices. Polymer brushes offer a broad variety of resources to manipulate interfacial properties and gain molecular control over the synergistic combination of materials. Many recent examples show that the rational integration of polymer brushes in hybrid nanoarchitectures greatly improves the performance of energy devices in terms of power density, lifetime and stability. Seen in this light, polymer brushes provide a new perspective from which to consider the development of hybrid materials and devices with improved functionalities. The aim of this review is therefore to focus on what polymer brush-based solutions can offer and to show how the practical use of surface-grafted polymer layers can improve the performance and efficiency of fuel cells, lithium-ion batteries, organic radical batteries, supercapacitors, photoelectrochemical cells and photovoltaic devices.